PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V/A SDN 8 API-API KECAMATAN BUKIT BATU KABUPATEN BENGKALIS - Dina Afriyanti; Zariul Antosa; Lazim N Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study aims to improve learning outcomes fifth grade IPA students V/a SDN 8 Api-api fires Bukit Batu subdistrict Bengkalis academic year 2014/2015. Improved student learning outcomes IPA seen through the “Aplication of Inquiry Learning Model”. This study was conducted in March 2015. This subjects were students of class V/a SDN 8 Api-api fires with the number of students 20 people consisting of 11 men and 9 women. This research was conducted in the classroom with 2 cycles. This instrument of this research is learning device cinsisting of syllabus, lesson plans, worksheets. Data collection instrument using a testin the form of sheets of observations and test result of learning. The data in this study will be analyzed. Data activity of students has increased each cycle op to 90% with very good category. Data student learning outcomes from a base score, daily tests I and II Dally Deuteronomy seen an increase, On the basis of the average scores obtained by students only 65, 05 of the KKM is determined that the Daily Deuteronomy 68. At first there was an increase became 71, 25. On Day II Deuteronomy occurred again increased to 74, 25. From these result it apipears that the implementation of inquiry learning model can improve learning outcomes fifth grade science students V/a SDN 8 Api-api fires Bukit Batu Subdistrict Bengkalis academic year 2014/2015.Keyword: Aplication of inquiry learning model, the Result of IPA